2013
DOI: 10.1021/om400365v
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Disilylated and Digermylated Germylenes

Abstract: The preparation of triethylphosphine adducts of cyclic disilylated or digermylated germylenes was achieved by reaction of 1,4-dipotassio-1,1,4,4-tetrakis(trimethylsilyl)tetramethyltetrasilane with GeBr2·(dioxane) and PEt3. Phosphine abstraction with B(C6F5)3 allowed formation of the base-free germylenes, which undergo 1,2-trimethylsilyl shifts to the germylene atom to form the respective silagermene or digermene, which further dimerize in [2 + 2] cycloadditions to tricyclic compounds. The reasons responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
106
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(117 citation statements)
references
References 31 publications
8
106
0
3
Order By: Relevance
“…As was observed before for other NHC-stabilized germylenes, 4448 adduct 10 is stable and does not show any tendency to rearrange to 9 .…”
Section: Resultssupporting
confidence: 81%
“…As was observed before for other NHC-stabilized germylenes, 4448 adduct 10 is stable and does not show any tendency to rearrange to 9 .…”
Section: Resultssupporting
confidence: 81%
“…24 In a subsequent contribution we demonstrated that the dimeric forms of these plumbylene and stannylene but also the respective PEt 3 adducts could be used to obtain group 4 metallocene plumbylene and stannylene complexes I and II . 25 …”
Section: Introductionmentioning
confidence: 94%
“…With the recent availability of germylene phosphine adducts 24 the question arose whether the addition of disilylated germylenes to group 4 metallocenes would lead to the respective germylene or digermene complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The halogenated silicon is kinetically protected by the sterical demand of the vicinal trimethylsilyl groups. While this environment has a stabilizing effect on the molecule [30,31], it also makes derivatization reactions more difficult. However, it was possible to synthesize the cyclopentasilane as well as the difluoro-, dichloro-, dibromo-, and diiodo-derivatives via one or two-step reaction procedures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of Kira's silylene is caused by sterically demanding trimethylsilyl-groups on the carbons in a,a'-position. The same protective groups have been used for the generation of germylenes, stannylenes and plumbylenes with only silicon atoms in the ring backbone [30,31].…”
Section: Introductionmentioning
confidence: 99%